Intracoronary Catheter Aspiration Can Be an Adequate Option in Patients with Acute Myocardial Infarction Caused by Left Atrial Myxoma - Park, Hyung Seo (Korean Society of Echocardiography, 2009)
Cardiac myxomas are the most common benign cardiac tumors and can be associated with systemic embolization including acute myocardial infarction (AMI). The probability of an arterial embolization is closely related to a tumor's villous morphology. In cases of AMI caused by cardiac myxoma, open heart surgery including excision of the coronary artery has been the one of the treatment options for removing the myxoma and embolus from the coronary artery to maintain distal coronary flow. However, preparing for emergent open heart surgery takes a considerable amount of time. Moreover, this time delay can deteriorate the coronary perfusion to the infarcted area and is associated with poor clinical prognosis. So intracoronary catheter aspiration can be an additional option to maintain the distal coronary flow. In this report we present a case with acute anterior ST elevation myocardial infarction caused by a left atrial myxoma. The embolus in the left anterior descending coronary artery was successfully removed with intracoronary catheter aspiration, and distal coronary flow was restored after the procedure.